Factors associated with watery diarrhoea diseases in under-five children in Chakari Mine of Sanyati District in Mashonaland West, Zimbabwe .September 2011. - George, Kambondo; Chadambuka, E.; Maxwell, Mhlanga; Ndaimani, Augustine (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Globally, there are about 3.2 million deaths worldwide in children under 5 years from diarrhoea every year (WHO, 2010). Child mortality and morbidity mostly results from contaminated food and water sources. Reported attack rates in developing countries range from 1 to 12 episodes per child per year. Kadoma District before it was split once experienced outbreak of diarrhoea in 2007 where 34 children under five years died. Chakari mine area experienced an increase of watery diarrhoea cases since week 26 from 6% to 17% by week 39 of September 2011. The increase was noticed on the 6th of September 2011 of which 74% of the cases were Children under the age of 5 years presenting with watery diarrhoea, fever and some with vomiting. We set out to describe the outbreak and identify risk factors and institute prevention and control measures. Methodology: An unmatched 1:1 case control was carried out. A case was any child under five years of age who presented with diarrhoea, with or without vomiting and other symptoms from the 6th of September 2011 and has been resident in Chakari mine for two weeks prior to onset of the symptoms. A diarrhoea case was defined as having passed three or more loose stools within 24 hours. Controls were any child who did not develop diarrhoea from the 6th of September up to the day of the interview, and has been a resident neighbour of Chakari mine for the previous two weeks. An interviewer administered questionnaire was used for data collection. Checklist for resources was used. Multivariate analysis for risk factors was done using EPI INFO V 3.5.3 statistical package. Results: A total of (76) case caregivers and (76) control caregivers were interviewed. Cold Sadza and cold porridge were statistically significant risk factors which were associated with contracting watery diarrhoea with Odds Ratio [13(95%CI 2.3, 71.7) p=0.00034] and [OR, 28.7(95% CI 2.2, 362.7)p=0.0096] respectively. Cold vegetables were protective from contracting diarrhoea with Odds Ratio [0.1(95% CI 0.01, 0.96) p=0.05]. Washing of hands in one bowl at home was the only independent risk factor which was statistically significant associated with contracting diarrhoea in Chakari mine at adjusted Odds Ratio [11.4(95% CI 1.86,70.1) p=0.008]. Discussion and Conclusion: Cold Sadza and cold porridge was the major risk factors associated with contracting watery diarrhoea in Chakari. The major finding indicated that the food was being contaminated by the practice of washing hands using the same bowl. The caregivers need health education on the importance of hand washing before eating using the run to waste method. The water for Chakari mine needs Chlorination to improve its quality.